Let us prey! Prey selection and dietary overlap amongst large predators in a semi-arid landscape, Hwange National Park, Zimbabwe. - Chatikobo, Simbarashe Pride (Midlands State University, 2017)
Comprehensive knowledge on the distribution and densities of large carnivores and their prey is necessary in order to understand conservation of carnivores and to mitigate human-wildlife conflict. In order to understand large carnivore ecologies, their diet, dietary overlap, niche breadth and seasonal variation was determined. Fecal analysis method was used in the determination of the diet of lions, leopards, cheetahs, wild dogs and hyenas was studied in a semi-arid savannah ecosystem of Hwange National Park, Zimbabwe. Fecal analysis revealed 20 Mammalian, 1 Rodentia and 1 Avian species ranging from small birds and rodents to large mammals. No domestic livestock prey item was found in the feces. The diet of the five large carnivores overlapped significantly. Large and medium-sized ungulates were the most frequent, with buffalo and impala being the most important prey species. Buffalo was the primary and secondary prey species for lions and hyenas respectively, and impala was the primary prey species for leopards, cheetahs, wild dogs and hyenas, and secondary prey species for lions. Diets of the carnivores significantly varied in the utilization of different prey-size categories (p < 0.05), large prey (>100 kg) contributed mostly to the diet of lions and hyenas, medium-sized prey (25-100 kg) contributed mostly to the diet of leopards and wild dogs, and small prey (5-25 kg) to the diet of cheetahs. Seasonal variation was not significant (p = 0.29) in the utilization of different prey size categories. For the diet of lions significant variation (p < 0.05) was detected in the large and medium-sized categories and no significant variation (p = 0.11) in the small sized category. Continuous annual investigations into the seasonal variations of diet selection by the large carnivores in Hwange National Park